VAMP7-dependent mitochondria–lysosome contacts contribute to glial mitochondrial dynamics and dopaminergic neuron survival - Honglei Wang; Mengxiao Wang; Yu-Ting Tsai; Yi-Hsuan Cheng; Yu-Tung Lin; Chia-Ching Lin; Yi-Hua Lee; Linfang Wang; Shuanglong Yi; Shiping Zhang; Yufeng Pan; Margaret S. Ho (Proceedings of the National Academy of Sciences, 2026)
Although disrupted mitochondrial dynamics in neurons are closely linked to neurodegenerative diseases, far less is known about how mitochondrial dynamics are regulated in glia or whether glial mitochondrial dysfunction contributes to neurodegeneration. Here, we show that the R-SNARE protein VAMP7 regulates the untethering of mitochondria–lysosome contacts (MLCs) in adult fly glia. Glial-specific knockdown of VAMP7 leads to prolonged MLCs and mitochondrial elongation associated with altered fission/fusion dynamics. These VAMP7-deficient mitochondria exhibit hyperpolarized membrane potential, leading to increased reactive oxygen species production, lipid droplet accumulation, and dopaminergic neurodegeneration. Mechanistically, VAMP7 interacts with the GTPase-activating protein TBC1D15-17 to promote Rab7 GTP hydrolysis. Without VAMP7, TBC1D15-17 remains bound to Rab7 but fails to activate its hydrolysis, resulting in elevated GTP-bound Rab7 and impaired MLCs untethering. Consistently, expression of GTP-locked Rab7 Q67L or GTPase-activating protein-dead TBC1D15-17 ΔGAP phenocopies the mitochondrial defects, while GDP-bound Rab7 T22N or wild-type TBC1D15-17 restores the MLC dynamics. Considering that SNARE proteins mediate membrane fusion, our results demonstrate a role for VAMP7 in glial mitochondrial dynamics via organelle contacts, impacting neuron survival in a non-cell-autonomous manner.